2015
DOI: 10.2527/jas.2014-8217
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × environment interaction for age at first calving, scrotal circumference, and yearling weight in Nellore cattle using reaction norms in multitrait random regression models

Abstract: ABSTRACT:The aim of this study was to verify the importance of genotype-environment interaction (GEI) for age at first calving (AFC), scrotal circumference (SC) and yearling weight (YW) in Nellore cattle, using reaction norms in multi-trait random regression models and analyze the efficiency of selection for AFC based on SC and YW in different environments. The research was conducted using 28,871, 41,386 and 89,152 records for AFC, SC and YW, respectively. Environmental groups (EGs) were defined based on farm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
28
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 27 publications
12
28
4
Order By: Relevance
“…The genetic correlations have been used to assess the degree of animal sensitivity to environmental changes (Robertson, ). These estimates are in agreement with other results reported by Santana et al (, ) and Chiaia et al (), in which the magnitude of genetic correlation estimates decreased when differences between EC levels increased, indicating the occurrence of G×E interaction with re‐ranking of EBVs across EC levels.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The genetic correlations have been used to assess the degree of animal sensitivity to environmental changes (Robertson, ). These estimates are in agreement with other results reported by Santana et al (, ) and Chiaia et al (), in which the magnitude of genetic correlation estimates decreased when differences between EC levels increased, indicating the occurrence of G×E interaction with re‐ranking of EBVs across EC levels.…”
Section: Resultssupporting
confidence: 93%
“…under less restrictive EC levels the genetic variance estimates increased. This tendency was previously described for SC (Santana et al ; Chiaia et al ) and HP (Santana et al ) in Nellore. The differences in heritability estimates at different EC levels occur as a consequence of the G×E interaction (Fordyce, ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…However, some authors have reported the existence of G × E in herds evaluated within the same country and among countries (Cardoso et al, 2011;Ambrosini et al, 2014). A more robust way to study G × E is through random regression models with reaction norm (Cardoso and Tempelman, 2012;Chiaia et al, 2015). Reaction norm models relate, linearly, the genetic merit of animals to changes in the environment gradient (EG) (Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that consider reaction norm models for beef cattle yearling weight (YW) evaluations have been conducted using pedigree and phenotypic information (Cardoso et al, 2011;Chiaia et al, 2015). The inclusion of molecular marker information can be beneficial for reaction norm models because the effect of each marker can be calculated in different environments, instead of assuming an average environment.…”
Section: Introductionmentioning
confidence: 99%